2022
DOI: 10.12932/ap-060919-0638
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme replacement therapy desensitization in a child with infantile onset Pompe disease

Abstract: Background: Enzyme replacement therapy significantly reduces morbidity and mortality in patients with Pompe disease. Development of hypersensitivity reactions to enzyme replacement therapy is common and can adversely affect disease outcomes when treatment is halted or delayed.Objective: Our institution reports a case of successful alglucosidase alfa enzyme replacement therapy desensitisation in a 9-year-old girl with infantile onset Pompe disease.Methods: A desensitisation protocol was tailored to our patient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
0
4
0
1
Order By: Relevance
“…Con respecto al tratamiento para las reacciones infusionales, se describen tres opciones. En primer lugar, la prevención y manejo estándar, donde se incluye la premedicación y la disminución de la velocidad de infusión; en segundo lugar, la inmunomodulación, cuyo objetivo es disminuir la respuesta de anticuerpos mediante la supresión de los linfocitos B, utilizando rituximab y metotrexate antes de administrar la primera dosis de alglucosidasa alfa en pacientes negativos para CRIM; y, finalmente, la desensibilización [17], con algunos casos reportados en la literatura para la desensibilización específica para la alglucosidasa alfa [3,[17][18][19][20][21][22].…”
Section: Discussionunclassified
“…Con respecto al tratamiento para las reacciones infusionales, se describen tres opciones. En primer lugar, la prevención y manejo estándar, donde se incluye la premedicación y la disminución de la velocidad de infusión; en segundo lugar, la inmunomodulación, cuyo objetivo es disminuir la respuesta de anticuerpos mediante la supresión de los linfocitos B, utilizando rituximab y metotrexate antes de administrar la primera dosis de alglucosidasa alfa en pacientes negativos para CRIM; y, finalmente, la desensibilización [17], con algunos casos reportados en la literatura para la desensibilización específica para la alglucosidasa alfa [3,[17][18][19][20][21][22].…”
Section: Discussionunclassified
“…Desensitization has been successfully described in laronidase (type-I mucopolyssacharidosis [MPS-I]), arylsulfatase B (MPS-VI), galsufase (MPS-VI), aglucosidase alfa (Pompe disease), and sebelipase alfa (lysosomal acid lipase deficiency) (Table 1). [36][37][38][39][40][41]…”
Section: Nonsteroidal Anti-inflammatory Drugsmentioning
confidence: 99%
“…As infusion-associated reactions of various mechanisms have similar presentation, clinicians are unable to use clinical history to predict these events and guide management [74]. After a potential hypersensitivity reaction has been identified, three approaches are possible: standard prevention and management, immunomodulation, and desensitization [75].…”
Section: Hypersensitivity Reactions To Ertmentioning
confidence: 99%
“…To our knowledge, 10 cases (8 pediatric, 2 adults) affected by Pompe disease and subjected to desensitization protocol have been reported [14,56,74,75,79,81,82] (Table 6). Of note, recently Emecen Sanli et al reported the first case of successful concomitant immunotolerance induction and desensitization protocol in a CRIM negative 7-month-old male patient, that have developed IARs and anti-rhGAA antibodies (1:12,800) [83].…”
Section: Mechanism Adverse Eventsmentioning
confidence: 99%
See 1 more Smart Citation